Portability of pension, health, and other social benefits: Facts, concepts, issues - Robert Holzmann; Johannes Koettl (Institute for the Study of Labor (IZA), 2011)
Portability of social benefits across professions and countries is an increasing concern for individuals and policy makers. Lacking or incomplete transfers of acquired social rights are feared to negatively impact individual labor market decisions as well as capacity to address social risks with consequences for economic and social outcomes. The paper gives a fresh and provocative look on the international perspective of the topic that has so far been dominated by social policy lawyers working within the framework of bilateral agreements; the input by economists has been very limited. It offers an analytical framework for portability analysis that suggests separating the risk pooling, (implicit or actual) pre-funding and redistributive elements in the benefit design and explores the proposed alternative approach for pensions and health care benefits. This promising approach may serve both as a substitute and complement to bi- and multilateral agreements.
urn:nbn:de:101:1-201105306410
Keywords: D91; F22; F53; G23; J61; 330; portability; acquired rights; migration; bilateral agreements; risk pooling